1001 movie posters designs of the times - Elangasinghe, Alison (Reel Art Press, an imprint of Rare Art Press Ltd., 2024)
"The most comprehensive overview of movie posters ever published, 1001 Movie Posters is a definitive coffee-table volume from world authority on the art form, Tony Nourmand. Spanning more than a century of global imagery, the book celebrates the most arresting, aesthetically powerful examples of the genre, including a number of posters that have never been published before".
Keywords: Geschichte 1896-2021; Filmplakat; Bildband